Expansion of typical lakes in Xinjiang under the combined effects of climate change and human activities - Wang, Wenqi; Jiao, Ayong; Shan, Qianjuan; Wang, Zikang; Kong, Zijie; Ling, Hongbo; Deng, Xiaoya (Frontiers in Environmental Science, 2022)
Lakes are important guarantees of regional economic development and ecological security. Previous studies focused on trends of surface area and water level of lakes in Xinjiang, but paid less attention to nonlinear change and driving mechanisms of lake areas at annual and monthly scales. To address this issue, this study used a remote-sensing Big Data cloud platform and mathematical statistical methods to investigate the change in typical lakes and its attribution in Xinjiang during 1986 to 2020. The results showed that: (1) there was a significant linear trend in Xinjiang lakes: except for Jili Lake, the plains lakes showed an insignificant (p>0.1) expansion trend, while the mountain lakes showed an significant expansion trend (p<0.01). (2) There was a significant nonlinear trend in Xinjiang lakes: most of the plains lakes showed periodicity at 14 and 21 years, however most of the mountain lakes showed periodicity at 17 and 21 years. Most of the mutation trends of plains lakes were not significant, yet the mutation trends of mountain lakes showed significant expansion. (3) Human activities were the dominant factor leading to changes in the plains lakes: among the anthropogenic factors, farmland area, GDP, and population had significant effects on lake area (p < 0.1), and lake expansion was closely related to population and farmland area. Among climatic elements, precipitation mainly affected the changes in plains lakes. (4) Climate change was the dominant factor leading to changes in mountain lakes. The effects of temperature change on mountain lakes were all significantly positive (p<0.05). In the future, it will be necessary to build lake protection schemes that adapt to climate change and human disturbances. This study can provide an important scientific basis for the rational development and utilization of lakes in Xinjiang.